Job loss fears and (extremist) party identification: First evidence from panel data - Ingo Geishecker; Thomas Siedler (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
There is a large body of literature analyzing the relationship between objective economic conditions and voting behavior, but there is very little evidence of how perceived economic insecurity impacts on political preferences. Using seventeen years of household panel data from the German Socio-Economic Panel, we examine whether job loss fears impact on individuals' party identification. Consistent with the deprivation theory, we find strong and robust evidence that subjective job loss fears foster affinity for parties at the far right-wing of the political spectrum. The effects are broadly comparable in direction and magnitude with the ones from objective unemployment and being out of the labor force. However, our empirical estimates do not suggest that job loss fears result in people withdrawing their support from political parties altogether or increasingly identify with extremist left-wing parties.
Keywords: J01; J63; P16; 330; job insecurity; party identification; prospective voting; economic worries